Viden om ... Hvad rummede en (old)islandsk ordbog for fem kvarte århundreder siden? - Helgadóttir, Fiorbjörg (Nordiske Studier i Leksikografi, 2003)
In 1839 a rich Englishman by the name of Richard Cleasby came to Copenhagen and started to learn Icelandic. In the spring of the following year, 1840, he came to an agreement with his teacher, Konráð Gíslason, that they should in partnership produce an Old Icelandic dictionary. Various Icelandic students were employed on the project, and in 1847 there were a number of draft articles available for inspection. Cleasby died in the same year, but his heirs asked Konráð Gíslason to continue with the project, which he did in co-operation with various assistants. In 1854 it appears that the heirs’ patience had run out and they arranged for the materials to be sent to England. What exactly these materials consisted of has been the subject of controversy ever since. In 1864, ten years later, an Icelandic philologist, Guðbrandur Vigfússon, undertook to prepare the manuscript for publication, and the dictionary was finally published in fascicle form in the years 1869-1874. A second edition, with a supplement, appeared in 1957. The paper discusses the gestation of the dictionary, which was christened ’An Icelandic-English Dictionary. Based on the Ms. Collections of the Late Richard Cleasby. Enlarged and completed by Gudbrand Vigfusson, M.A.’